The Role of Green Sukuk in Achieving the Sustainable Development Goal of Climate Action: The Case of Saudi Arabi (2020-2025) - Alamoudi, Abdulrhman Mohmmad; Alhasani, Sheikha Mahisn; Bahakim, Nada Mohammed (Journal of Economic, Administrative and Legal Sciences, 2025)
Several countries are facing major challenges due to their arid climate, such as the Kingdom of Saudi Arabia, which also suffers from the scarcity of water resources, as climate change and heat stress are among the most prominent challenges that negatively affect the capacities these countries. For example, rising temperatures are also affecting public health, leading to an increase in illnesses and respiratory diseases. Green financing plays an important role in achieving many social development goals. The importance of the research can be seen in its focus on the role of green financing instruments in achieving social development goals and, in particular, highlights the contribution of green sukuk to achieving one of the key economic development goals of climate action. The results show that several countries are focusing on green sukuk to finance their projects. Saudi Arabia is one of the largest issuers of green Sukuk, which is a mark of radical support for projects and for reducing carbon dioxide emissions.
Keywords: Sustainable Development; Green Sukuk; Climate Action